93 pi Krasuang Suksathikan. - Thailand. Krasuang Suksathikan ([Bangkok] : Krasuang Suksathikan, 1985)
Commemorative volume for Ministry of Education's 93rd anniversary; comprises its policies and activities.
"1 Mesayaon 2528"--Cover.
Keywords: Thailand. -- Krasuang Suksathikan; Education and state -- Thailand